2022
DOI: 10.1590/fst.55320
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influence on centesimal composition and yield of Amazonian fish

Abstract: The objective of this study was to evaluate meat yield and centesimal composition of the Amazonian fish species, A. ocellatus, P. castelnaeana, and L. friderici, in the dry and flood seasonal cycles of rivers. In each seasonal cycle (flood and dry), a total of 60 fish were collected, comprising 20 specimens of each of the following species: A. ocellatus, P. castelnaeana, and L. friderici. Were evaluated the meat yield, cuts yield and centesimal composition of the fish samples. Meat yield in the clean body cuts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This value is lower than Souza and Inhamuns (2011) found when analyzing the same species, with average values of 3.92% and 6.33%, respectively. Barai et al (2022), in the flood and drought period, obtained higher yields than those reported in the study when evaluating the skin of the Amazonian species Astronatus ocellatus (Agassiz, 1831), Pellona castelnaeana (Valenciennes, 1847) and Leporinus friderici (Bloch, 1794). Meanwhile, for marine catfish Sciades herzbergii (Bloch, 1794), the value was higher (6.2%) than that of the current study (Vasconcelos-Filho et al, 2017).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…This value is lower than Souza and Inhamuns (2011) found when analyzing the same species, with average values of 3.92% and 6.33%, respectively. Barai et al (2022), in the flood and drought period, obtained higher yields than those reported in the study when evaluating the skin of the Amazonian species Astronatus ocellatus (Agassiz, 1831), Pellona castelnaeana (Valenciennes, 1847) and Leporinus friderici (Bloch, 1794). Meanwhile, for marine catfish Sciades herzbergii (Bloch, 1794), the value was higher (6.2%) than that of the current study (Vasconcelos-Filho et al, 2017).…”
Section: Resultsmentioning
confidence: 51%
“…According to Barai et al (2022), these differences in yield occur due to the morphometry of the species, which is essential data for the fish industries to avoid waste and add value to the by-product generated. In addition, the skin yield will depend on the operator's skill, so there are no excessive losses during this skin removal process (Oliveira Filho et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In Salvelinus fontinalis Mitchill, Salmo trutta Linnaeus, 1758, and hybrid trout, differences in carcass yield were approximated by fat content (Şahin et al 2011). The same method was used for Astronotus ocellatus Agassiz, Pellona castelnaeana Valenciennes, and Leporinus friderici Bloch (Barai et al 2022). We did not analyze fat content, but the EOLG may have influenced the fish body composition and, consequently, the carcass yield.…”
Section: Discussionmentioning
confidence: 99%
“…Little is the known about the nutritional value of these species, and how these influence the diet of the Amazon people. Recently, some studies were developed to understand and solve these research gaps, such as Yuyama et al (2011) and Tavares et al (2012) that carried out nutritional studies in several cities across the Amazonas state and detected a deficiency in some nutrients; while Barai, Souza, Viana, and Inhamuns (2021) evaluated meat yield and centesimal composition of some of the main Amazonian fish species in the drought and flood hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%